Anaerobic Activation of p-Cymene in Denitrifying Betaproteobacteria: Methyl Group Hydroxylation versus Addition to Fumarate - Strijkstra, Annemieke (Appl Environ Microbiol, 2014)
The betaproteobacteria “Aromatoleum aromaticum” pCyN1 and “Thauera” sp. strain pCyN2 anaerobically degrade the plant-derived aromatic hydrocarbon p-cymene (4-isopropyltoluene) under nitrate-reducing conditions. Metabolite analysis of p-cymene-adapted “A. aromaticum” pCyN1 cells demonstrated the specific formation of 4-isopropylbenzyl alcohol and 4-isopropylbenzaldehyde, whereas with “Thauera” sp. pCyN2, exclusively 4-isopropylbenzylsuccinate and tentatively identified (4-isopropylphenyl)itaconate were observed. 4-Isopropylbenzoate in contrast was detected with both strains. Proteogenomic investigation of p-cymene- versus succinate-adapted cells of the two strains revealed distinct protein profiles agreeing with the different metabolites formed from p-cymene. “A. aromaticum” pCyN1 specifically produced (i) a putative p-cymene dehydrogenase (CmdABC) expected to hydroxylate the benzylic methyl group of p-cymene, (ii) two dehydrogenases putatively oxidizing 4-isopropylbenzyl alcohol (Iod) and 4-isopropylbenzaldehyde (Iad), and (iii) the putative 4-isopropylbenzoate-coenzyme A (CoA) ligase (Ibl). The p-cymene-specific protein profile of “Thauera” sp. pCyN2, on the other hand, encompassed proteins homologous to subunits of toluene-activating benzylsuccinate synthase (termed [4-isopropylbenzyl]succinate synthase IbsABCDEF; identified subunits, IbsAE) and protein homologs of the benzylsuccinate β-oxidation (Bbs) pathway (termed BisABCDEFGH; all identified except for BisEF). This study reveals that two related denitrifying bacteria employ fundamentally different peripheral degradation routes for one and the same substrate, p-cymene, with the two pathways apparently converging at the level of 4-isopropylbenzoyl-CoA.